(untitled) (European Journal of Pure and Applied Mathematics, 2024)
For any filter of a paradistributive latticoid, () is defined and it is proved that () is a filter if is prime. It is also proved that each minimal prime filter belonging to () is contained in , and () is the intersection of all the minimal prime filters contained in . The concept of a normal paradistributive latticoid is introduced and characterized in terms of the prime filters and minimal prime filters. We proved that every relatively complemented paradistributive latticoid is normal.